Addressing Vulnerable Population Needs in the Last Mile to the elimination of mother to child transmission of HIV: (Re)Claiming the HIV Response for Female Sex Workers and Their Children - Avi J. Hakim; Tegan Callahan; Irene Benech; Monita Patel; Michelle Adler; Surbhi Modi; Moses Bateganya; Kae Anne Parris; Trista Bingham (BMC, 2020)
Abstract As countries strive to eliminate mother-to-child transmission of HIV, female sex workers (FSW) and their children still face barriers to accessing these essential services. Data on FSW uptake of HIV and reproductive health services before, during, and after pregnancy reveal inadequate service utilization. Stigma encountered by FSW in healthcare settings may contribute to low uptake of HIV testing, antiretroviral therapy (ART), and other prevention of mother-to-child HIV transmission (PMTCT) services. Coordination between community-based FSW and facility-based PMTCT programs can facilitate successful linkage of pregnant FSW to antenatal services to support PMTCT efforts. We offer a way forward to reach 90-90-90 targets for FSW and their families and eliminate mother-to-child transmission of HIV.